THE ARRIVAL OF CATHOLIC CHURCH IN THE ANGAMI AREA IN NAGALAND - *, KETHOLESIE (IJRDO-Journal of Applied Science, 2015)
This paper makes an attempt to trace some of the important events leading to the arrival of the Catholic Church in the Angami area and also the contribution of the Church to the overall development of the Angami Nagas. Christianity in Nagaland began with the arrival of the American Baptist missionaries in Upper Assam, extending their mission into the Hills. There are several Christian denominations working in Nagaland such as the Catholics, the Baptists, the Christian Revival Church, the Assembly of God, the Pentecostal, the Seventh Day Adventist and the Jehovah Witnesses.